The imbrication between maxiprocesses and cooperation agreement: the displacement of the information center to the preliminary investigation in “Lava Jato Operation” - Antonio Eduardo Ramires Santoro (Revista Brasileira de Direito Processual Penal, 2020)
The “Lava Jato Operation” has maximized features and cooperation agreement has been used as the primary instrument in evidence production. From this context, the following problem arises: Is there an intrinsic relationship between maxiprocesses and cooperation agreement that shifts the process information center from the procedural instructional to the preliminary investigation on “Lava Jato Operation”? The initial hypothesis is that cooperation agreement is a hallmark of maxiprocesses, and the factual information that forms the judgment of the judge is produced during the preliminary investigation. The research was conducted by the deductive method, at a substantially exploratory and partially descriptive level, from bibliographic sources especially about maxiprocesses and cooperation agreement, as well as empirical research from documentary sources of two major judicial processes that make up the police-investigative complex / procedural-court which is “Lava Jato Operation”.